Colorado's Model for Preparing Paraprofessionals for Rural Early Intervention Programs. (March 2013) - Chopra, Ritu; Banerjee, Rashida; Dipalma, Geraldine; Merrill, Laura; Ferguson, Ardith
Under the supervision of a licensed early intervention provider, paraprofessionals play an indispensable role in implementation of home and community-based services to infants and toddlers with developmental delays or disabilities and their families in Colorado. The Individuals with Disabilities Education Act of 2004 requires that paraprofessionals be appropriately trained for their unique roles; however, early intervention paraprofessionals, particularly in rural areas, have limited access to quality preparation programs. This article shares an example of a statewide model of preparation and training for early intervention paraprofessionals. The outcomes achieved, lessons learned, and next steps in the implementation of the model are also presented.